Histological Changes In Placentae In Pregnancies Complicated By Pre-Eclampsia And Eclampsia And Corelation With Foetal Outcome - PASRICHA NAVBIR; NAGAR ALKA; GUPTA ANTIMA (International Journal of Pharma and Bio Sciences, 2012)
Pre eclampsia, the clinical state prior to full blown eclampsia (siezures), is one of the toxemias of pregnancy. The basic clinical definition is that it is a pregnancy specific condition of increased blood pressure accompanied by proteinuria, edema or both. Many phenomena have been investigated, but the recurring theme appears to be an abnormally low blood flow into the placenta. The present study was designed to determine the histological changes in pregnancies complicated by pregnancy induced hypertension and to correlate the changes with foetal outcome. A study of sixty placentae was done with the collaboration of Department of Obstetrics and Gynaecology, to find out the histological changes of placenta in 30 women suffering from pregnancy induced hypertension in comparison to 30 women with uncomplicated gestation. The main histological features noted were cytotrophoblastic proliferation, basement membrane thickening, vasculosyncytial membrane deficiency which correlated well with the foetal outcome. The other features noted were syncytial knot formation, fibrinoid necrosis and stromal fibrosis.